Propuesta de un modelo pedagógico curricular basado en la educación emocional para los alumnos de la especialidad de educación primaria de la Universidad Nacional de Trujillo - Burgos Goicochea, Saby (2015)
The following research is aimed to develop a proposal for a curricular teaching model based on Emotional Education for students of the Specialty of Primary Education of the National University of Trujillo. The proposal made is part of a humanistic approach and is determined by the competency-based training, the same that seeks to promote the emotional development of students as an essential complement of cognitive development, which both constitute the essential elements of comprehensive student’s personality. The research was conducted considering a diagnostic evaluation to determine the sensitive elements of the existing model in the School and the results obtained in the Scale of Teacher Performance Assessment and Inventory of Emotional Intelligence BarOn ICE: NA, applied to 116 students from the second, third and fourth years of Primary Education that formed the sample, the same that establish a high degree of association between the perception that these have on the professional and personal characteristics of teachers who work in schools and handling the emotional skills of the student.